Cultivation of Chlorella sp. GD using piggery wastewater for biomass and lipid production. (October 2015) - Kuo, Chiu-Mei; Chen, Tsai-Yu; Lin, Tsung-Hsien; Kao, Chien-Ya; Lai, Jinn-Tsyy; Chang, Jo-Shu; Lin, Chih-Sheng
Graphical abstract: Highlights: Piggery wastewater was able to be directly used for Chlorella sp. GD cultivation. The maximum specific growth rate of Chlorella sp. GD with 100% piggery wastewater was 0.839 d −1 . The biomass and lipid productivity of Chlorella sp. GD was enhanced in a semi-continuous culture. Stable growth performance for long-term microalgal cultivation in semi-continuous operations is promising. Abstract: The development of a culture system for Chlorella sp. GD to efficiently produce biomass and oil for biodiesel production was investigated. Chlorella sp. GD was cultivated with 0%, 25%, 50%, 75% and 100% piggery wastewater (diluted by medium) at 300 μmol m −2 s −1, a 2% CO2 aeration rate of 0.2 vvm and 26 ± 1 °C; after a 10-day culture in batch cultures, the maximum specific growth rate and biomass productivity of the microalga obtained in 100% piggery wastewater were 0.839 d −1 and 0.681 g L −1 d −1, respectively. The highest lipid content and lipid productivity were 29.3% and 0.155 g L −1 d −1 at 25% wastewater, respectively. In semi-continuous cultures, the biomass and lipid productivities with 25–75% wastewater ratios were greater than 0.852 and 0.128 g L −1 d −1, respectively. These results show that Chlorella sp. GD grows efficiently in piggery wastewater, and that a stable growth performance was achieved for long-term microalgal cultivation in a semi-continuous culture.